Analisis Struktur Impor Smartphone di Indonesia : Studi 5 Negara Pengimpor Utama (Tahun 2025) - Zahra Intan Nur Adila (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
Smartphones are one of the most demanded technology products in Indonesia. To meet this demand, Indonesia relies heavily on imports from various countries. This study aims to analyze the structure of smartphone imports in Indonesia based on the top five importing countries in 2025. The study uses a descriptive quantitative approach with secondary data obtained from the Central Bureau of Statistics. The results show that China dominates smartphone imports to Indonesia, followed by Singapore, the United States, Hong Kong, and Malaysia. This dominance indicates a high dependency on a single country, which has implications for trade policy and economic resilience.